Epidemiological, pathological and microbiological study of equine dental caries - Borkent, Dewi (The University of Edinburgh, 2018)
Dental caries is caused by acidogenic oral micro-organisms which convert fermentable carbohydrates to acids that damage the tooth by causing a demineralisation and disintegration of the inorganic and organic substances of the tooth, respectively (Soames and Southam, 2005). In horses, two variants of dental caries occur: equine dental peripheral caries (PC) involving the periphery of teeth; and infundibular caries (IC) of the maxillary cheek teeth. Twenty-five veterinarians and equine dental technicians experienced in equine dentistry were recruited to perform a UK-wide survey and examined 706 horses for the presence PC and IC, as well as for concurrent dental disorders. The recorded survey results for individual horses included data on potential risk factors including breed, sex, age, diet and the postcode of stables. The prevalence of PC and IC in this population, was 51.7% and 45.5%, respectively. The most commonly and severely PC affected teeth were the three caudal cheek teeth (Triadan 09-11) and for IC were the Triadan 09s. In a multivariable model without observer as a random effect, potential risk factors for the development of PC were: the presence of IC, the presence of diastema/periodontal disease (PD), the presence of multiple concurrent dental disorders other than IC, being fed 2.1-3.0 kg concentrates per day, and living in South East England and South West England. The risk factors which remained significantly associated with the presence of PC in a multivariable model with observer as a random effect, were: feeding 2.1-3 kg concentrates per day, multiple concurrent dental disorders other than IC, the presence of diastema/periodontal disease; additionally, dental fractures now became significantly associated with the presence of PC. In a multivariable model without observer as a random effect, potential risk factors for the development of IC were: the presence of PC, the presence of multiple dental disorders other than IC, and increasing age. Horses in North England and South West England were significantly less likely to have IC than horses in other regions of England and Scotland. In a multivariable model with observer as random effect, the only remaining risk factors were increasing age and geographical region, with a significantly lower likelihood for horses to have IC in South West England than in the other regions. A molecular microbiological study on equine dental caries using a linear discriminant analysis effect size (LEfSe) at genus or higher level, showed Gemella and Actinobacillus to be the genera most associated with the PC study control group (no PC), and Streptococcus, Olsenella and Scardovia to be the genera most associated with PC. Additionally if LEfSe was performed at genus level only, then an additional genus shown to be associated with PC was Mitsuokella. The genus most associated with IC using LEfSe at genus or higher level was Acidaminococcus, while Bacillus was the genus most associated with the IC study control group (no IC). A pathological study examined PC-affected cheek teeth grossly, histologically and, by scanning electron microscopy (SEM) and transmission electron microscopy (TEM). Dental plaque, containing bacteria was found to cover the PC lesions. In peripheral cementum, PC lesions were categorised by their shape on histological cross sections of affected teeth into: flake-type, flask-like, or ellipsoid-shaped lesions or combinations of these patterns. Bacteria from surface lesions penetrated between Sharpey’s fibers of cementum in a direction perpendicular to the peripheral aspect of the tooth, destroying the intrinsic fibres and Sharpey’s fibers. Bacteria also penetrated in a direction parallel to the peripheral aspect of the tooth, undermining the intrinsic fibres, including at the level of incremental growth lines. Bacteria were also found in ellipsoid-shaped lesions and in cemental lacunae of affected cementum. In dentine affected by PC, bacteria were found within and between damaged dentinal tubules, sometimes causing flake-type lesions similar to those seen in cementum. Bacteria penetrated primary dentine and/or (regular/irregular) secondary dentine from the occlusal surface, or entered primary dentine through cementum and enamel from the peripheral aspect. Dental plaque containing bacteria were sometimes observed in dentinal fissure fractures. PC of enamel was only visible using SEM, because this was the only method which did not require prior decalcification, that almost completely removed enamel. In conclusion, PC and IC are prevalent dental disorders in the examined British equine population. The association between PC and concurrent dental disorders (multiple concurrent dental disorders, diastemata/periodontal disease and dental fractures), indicates that these should be addressed in affected horses. In horses affected by IC, the focus should be on treatment of IC itself (like infundibular fillings), because associations of IC were found with risk factors which cannot (or not easily) be controlled such as age and region. Several bacteria could be identified which were associated with PC and other bacteria were more associated with IC or control groups. It was confirmed in the pathological study that bacteria penetrate the cheek teeth affected by PC and IC. So the focus of treatment of PC and IC can also be on reducing the bacteria associated with PC and IC respectively, or the focus could be on prevention by making the teeth more resistant against caries by fluoride treatment. A critical assessment of the use of chlorhexidine mouthwashes and supplementation of fluoride are needed to evaluate its potential effects on PC and IC.
Keywords: dental caries; equine dental peripheral caries; infundibular caries; Gemella; Actinobacillus